2021
DOI: 10.48550/arxiv.2106.12465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Linear Cutting Blocking Sets and Minimal Codes in the Rank Metric

Abstract: This work investigates the structure of rank-metric codes in connection with concepts from finite geometry, most notably the q-analogues of projective systems and blocking sets. We also illustrate how to associate a classical Hamming-metric code to a rank-metric one, in such a way that various rank-metric properties naturally translate into the homonymous Hamming-metric notions under this correspondence. The most interesting applications of our results lie in the theory of minimal rank-metric codes, which we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…This connection has been intensively used to get classification results and intriguing constructions in both the areas of coding theory and finite geometry. Recently, in [38,41] it has been shown that equivalence classes of nondegenerate rank-metric codes are in one-to-one correspondence with equivalence classes of q-systems, where the latter constitute the q-analogue of projective systems; see also [1]. At this point, it is natural to ask whether it is possible to construct geometric objects able to capture the structure of sum-rank metric codes which generalize both projective systems and q-systems.…”
Section: Geometry Of Sum-rank Metric Codesmentioning
confidence: 99%
See 1 more Smart Citation
“…This connection has been intensively used to get classification results and intriguing constructions in both the areas of coding theory and finite geometry. Recently, in [38,41] it has been shown that equivalence classes of nondegenerate rank-metric codes are in one-to-one correspondence with equivalence classes of q-systems, where the latter constitute the q-analogue of projective systems; see also [1]. At this point, it is natural to ask whether it is possible to construct geometric objects able to capture the structure of sum-rank metric codes which generalize both projective systems and q-systems.…”
Section: Geometry Of Sum-rank Metric Codesmentioning
confidence: 99%
“…A first intuition was given in [40], while a full correspondence was provided in [41] and in [38]: kdimensional rank-metric codes over an extension field F q m of F q correspond to q-systems, which are special F q -subspaces of F k q m . This correspondence allowed us to give a complete characterization of nondegenerate F q m -linear one-weight codes in the rank metric; see [38,Theorem 12], [1,Proposition 3.16].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, consider the vector u whose i-th entry is x, j-th entry is y and all the other entries are zero and the vector u ′ whose i-th entry is x ′ , j-th entry is y ′ and all the other entries are zero, whereas x, y, x ′ , y ′ are nonzero. By (1) we obtain u = λu ′ , a contradiction to a). Now, suppose that ii) holds.…”
Section: Structure and Properties Of Multi-sidon Spacesmentioning
confidence: 83%
“…Let G be a matrix in F r× rn 2 q m whose columns are a basis of U . As a consequence of Theorem 7.16 and the connection between linear rank metric codes and q-systems (see [28] and also [1]), the linear rank metric codes having as a generator matrix G have exactly three nonzero weights, which are n − r, n − 1, n. In particular, they are examples (r − 1)-almost MRD codes, see [12]. Moreover, using [1, Theorem 4.8], we can from L U we can also construct linear Hamming metric codes with only three weight and for which we can completely establish its weight distribution, as already done for some classes of linear sets (see also [25,33]).…”
Section: More Preciselymentioning
confidence: 91%
See 1 more Smart Citation